Ultra‐pH‐Responsive and Tumor‐Penetrating Nanoplatform for Targeted siRNA Delivery with Robust Anti‐Cancer Efficacy. (3rd May 2016) - Xu, Xiaoding; Wu, Jun; Liu, Yanlan; Yu, Mikyung; Zhao, Lili; Zhu, Xi; Bhasin, Sushant; Li, Qing; Ha, Emily; Shi, Jinjun; Farokhzad, Omid C.
Abstract: RNA interference (RNAi) gene silencing technologies have shown significant potential for treating various diseases, including cancer. However, clinical success in cancer therapy remains elusive, mainly owing to suboptimal in vivo delivery of RNAi therapeutics such as small interference RNA (siRNA) to tumors. Herein, we developed a library of polymers that respond to a narrow pH change (ultra‐pH‐responsive), and demonstrated the utility of these materials in targeted and deep tumor‐penetrating nanoparticle (NP) for in vivo RNAi. The new NP platform is mainly composed of the following key components: i) internalizing RGD (iRGD) to enhance tumor targeting and tissue penetration; ii) polyethylene glycol (PEG) chains to prolong blood circulation; and iii) sharp pH‐responsive hydrophobic polymer to improve endosome escape. Through systematic studies of structure–function relationship, the optimized RNAi NPs (<70 nm) showed efficient gene silencing and significant inhibition of tumor growth with negligible toxicities in vivo.